Digital Comic Media Development Mappalili Culture in Essays Student Narrative - Nuriska Nuriska; Khaerun Nisa'a Tasyibu Nisa'a Tasyibu; Firdha Razak (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2026)
Problems in learning narrative essays in elementary schools are often related to the lack of contextual and interesting learning media. This research aims to develop Mappalili Culture-Based Digital Comic Media that is valid, practical, and effective. This study uses the Research and Development (R&D) method with ADDIE design involving 13 students in grade V of SD Negeri 1 Labakkang (5 males and 8 females). The instruments used included expert validation sheets, digital comic media, activity implementation sheets, student and teacher response questionnaires, and learning outcome tests. The results of the study show that digital comic media is in the category of valid, practicality is considered positive, effectiveness is proven through high learning outcomes, excellent implementation of student activities, and positive student and teacher responses. Thus, this media has been successfully developed with an ethnomathematical approach that can integrate the local culture of Bugis Makassar through the Mappalili tradition in learning narrative essays.